Pengembangan sistem pengontrolan konduktivitas listrik larutan berbasis internet of things untuk tanaman hidroponik (Development of the electrical conductivity control system in the solution based on the internet of things for hydroponic plants) - Weli Erlina; - Asrizal (PILLAR OF PHYSICS, 2020)
Hydroponics has become an alternative for people who want to garden, but they didn’t have enough space to grow crops. The most important problem that must be considered in hydroponic cultivation is the provision of adequate nutrition for plants. Inappropriate electrical conductivity values will result in undesirable things. Controlling conductivity in plants hydroponically is required so that the plants get the value of conductivity that accordingly. The purpose of the research is to determine the performance spesifications of the electrical conductivity control system, determine the effect of adding AB Mix solution to the conductivity and output voltage values, determine the accuracy and precision of the electrical conductivity control system on laboratory scale tests, and determine the results field scale test on the conductivity control system. This research is classified as research and development which is a research method used to develop products. Based on the results of data analysis, it can be concluded that there are four research data results. First, performance specifications which consist of sensors to measure electrical conductivity values, a circuit box containing a Node Mcu and a relay to drive the solenoid valve in the event of control. Second, the effect of adding AB Mix is directly proportional to the value of the conductivity. This means that the more the addition of solution AB Mix then the greater value output voltage. Meanwhile, the determine of the output voltage value the greater with the addition of solution AB Mix. Third, the results of the accuracy and presicion of the electrical conductivity control system of 98.98% and 97.40%. That is, the measurement and control data can be used because it is close to 100%. Third, the results of field scale tests that have been carried out for 3 days get varied data. Electrical conductivity values obtained during the field scale tests from 690 ppm up to 945 ppm.